Expansion of chemical space for collaborative lead generation and drug discovery: the European Lead Factory Perspective. Issue 11 (November 2015) - Karawajczyk, Anna; Giordanetto, Fabrizio; Benningshof, Jorg; Hamza, Daniel; Kalliokoski, Tuomo; Pouwer, Kees; Morgentin, Remy; Nelson, Adam; Müller, Gerhard; Piechot, Alexander; Tzalis, Dimitrios
Highlights: High-quality compound collections are a main determinant of drug discovery success. Generation of relevant collections is a significant challenge for any organization. The European Lead Factory employs a consortium approach to address this challenge. This has produced novel, diverse and complex compounds with reduced lipophilicity. Abstract : High-throughput screening (HTS) represents a major cornerstone of drug discovery. The availability of an innovative, relevant and high-quality compound collection to be screened often dictates the final fate of a drug discovery campaign. Given that the chemical space to be sampled in research programs is practically infinite and sparsely populated, significant efforts and resources need to be invested in the generation and maintenance of a competitive compound collection. The European Lead Factory (ELF) project is addressing this challenge by leveraging the diverse experience and know-how of academic groups and small and medium enterprises (SMEs) engaged in synthetic and/or medicinal chemistry. Here, we describe the novelty, diversity, structural complexity, physicochemical characteristics and overall attractiveness of this first batch of ELF compounds for HTS purposes.